Chryseobacterium indologenes Septicemia in an Infant - Aydin Teke, Turkan (Hindawi Publishing Corporation, 2014)
Chryseobacterium indologenes is a rare cause of infection in children. The organism causes infections mostly in hospitalised patients with severe underlying diseases. The choice of an effective drug for the treatment of infections due to C. indologenes is difficult as the organism has a limited spectrum of antimicrobial sensitivity. We present a case of nosocomial septicemia caused by C. indologenes in an infant with congenital heart disease who was successfully treated with trimethoprim sulfamethoxazole and also reviewed fourteen additional cases of C. indologenes infections reported in the English literature in this report.